Agricultural Water Management Problems in Hatay (Turkey) - Bekir Demirtaş; Erdal Dağıstan; Yalçın Yılmaz; Nuran Tapkı (Turkish Journal of Agriculture: Food Science and Technology)
This research was completed in 2014, in an attempt to determine the problems and solutions of the irrigation unions and their members who operate in the city of Hatay. The research involves 6 out of 8 irrigation unions located in Hatay. The data was gathered by face to face surveys conducted with 6 union managers and 173 union members. Logistics Regression analysis, which is a multivariate analysis technic was used in the analysis of the variables. It was concluded that 65% of the producers are satisfied, and 35% of them are unsatisfied with the irrigation union. The estimate parameters revealed that the irrigation price at low and normal level were the most effective variables. In accordance with the data, evaluated for the managerial staff in the permanent status, showed that the lack of the efficient and subject expert personnel is one of the most important issues directly interfering with the provided service. The delays occurring in the collection of the price of the irrigation water disrupts the maintenance services needed while operating the facilities. The unions need public assistance to cover the personnel expenses, large maintenance processes, and development of the facilities.